Blind parents and nutrition of children: experiences and care - Kariane Gomes Cezario; Paula Marciana Pinheiro de Oliveira; Albertina Antonielly Sydney de Sousa; Quitéria Clarice Magalhães Carvalho; Viviane Peixoto dos Santos Pennafort; Letícia Adriana Pires Ferreira dos Santos (Rev Rene)
Objective: to understand the experiences of blind parents in care related to breastfeeding and complementary feeding of children. Methods: qualitative research with the participation of four blind mothers and five blind fathers. Home interviews were carried out to address the experience of feeding children in the context of blindness, categorized by the technique of thematic analysis. Results: Three categories emerged: Breastfeeding and complementary feeding offered by blind mothers; Blind fathers and the feeding of children; and Care of the children and blindness: coping strategies, in which difficulties and alternatives developed to feed the children were highlighted. Conclusion: blind parents have difficulties similar to those seer parents but with specific demands associated with the handling of utensils in safe and satisfactory supply of food.